Clindamycin induced toxic epidermal necrolysis versus Staphylococcal scalded skin syndrome: a case report. Issue 3 (6th May 2020) - Davey, Matthew G; Birrane, John; Brennan, Michelle; Breen, David P; Laing, Mary E
Abstract: Toxic epidermal necrolysis and Staphylococcal scalded skin syndrome (SSSS) are potentially life-threatening dermatological emergencies that present in a similar clinical fashion. Toxic epidermal necrolysis is typically triggered by anticonvulsant and other neurological medications and reports clindamycin inducing the disease is exceedingly rare. SSSS seldomly occurs in adult patients. We present the case of a 60-year-old male presenting with dermatological rash covering >80% his body surface. Diagnosis and therapy involved multidisciplinary contribution from medical physicians, dermatologists, microbiologists and histopathologists to provide a favourable outcome.